Pharmaceutical Preparation of Modified Form of Gairikadi Anjana w.s.r to Ophthalmic Ointment - Das, Arun; Biradar, A B; Mannur, V S; Prakash, Prathibha (International Research Journal of Ayurveda & Yoga, 2022)
Background – Anjana (Collyrium) is a classical therapeutic procedure explained in context of maintaining health of healthy individuals. It is indicated in almost all diseases explained in classics starting from Jwara (Fever), Visha (Poisoning), till Shalakya tantra (treatment of disorders above clavicle) related disorders. Lack of proper commercial pharmaceutical dispensing form and unexplored clinical utility of Anjana (Collyrium) made its concept doubtful / un-explored. Methodology – Here, is an attempt made to bring Anjana (Collyrium) in practice with utility of modern pharmaceutical preparation without disturbing classical principles. Single Batch of Ointment was prepared. Result – The ointment was prepared (Single batch) under all aseptic conditions and microbial analysis was done and was clinically tried and found effective. Conclusion – Gairikaadi Anjana can be successfully turned into an Ophthalmic Ointment and was proven clinically effective.